MRI in the diagnosis of fetal developmental brain abnormalities: the MERIDIAN diagnostic accuracy study - Griffiths, Paul D; Bradburn, Michael; Campbell, Michael J; Cooper, Cindy L; Embleton, Nicholas; Graham, Ruth; Hart, Anthony R; Jarvis, Deborah; Kilby, Mark D; Lie, Mabel; Mason, Gerald; Mandefield, Laura; et al. (Health technology assessment (Winchester, England), 2019)
Ultrasonography has been the mainstay of antenatal screening programmes in the UK for many years. Technical factors and physical limitations may result in suboptimal images that can lead to incorrect diagnoses and inaccurate counselling and prognostic information being given to parents. Previous studies suggest that the addition of in utero magnetic resonance imaging (iuMRI) may improve diagnostic accuracy for fetal brain abnormalities. These studies have limitations, including a lack of an outcome reference diagnosis (ORD), which means that improvements could not be assessed accurately. To assess the diagnostic impact, acceptability and cost consequence of iuMRI among fetuses with a suspected fetal brain abnormality. A pragmatic, prospective, multicentre, cohort study with a health economics analysis and a sociological substudy. Sixteen UK fetal medicine centres. Pregnant women aged ≥ 16 years carrying a fetus (at least 18 weeks' gestation) with a suspected brain abnormality detected on ultrasonography. Participants underwent iuMRI and the findings were reported to their referring fetal medicine clinician. Pregnancy outcome was followed up and an ORD from postnatal imaging or postmortem autopsy/imaging collected when available. Developmental data from the Bayley Scales of Infant Development and questionnaires were collected from the surviving infants aged 2-3 years. Data on the management of the pregnancy before and after the iuMRI were collected to inform the economic evaluation. Two surveys collected data on patient acceptability of iuMRI and qualitative interviews with participants and health professionals were undertaken. The primary analysis consisted of 570 fetuses. The absolute diagnostic accuracies of ultrasonography and iuMRI were 68% and 93%, respectively [a difference of 25%, 95% confidence interval (CI) 21% to 29%]. The difference between ultrasonography and iuMRI increased with gestational age. In the 18-23 weeks group, the figures were 70% for ultrasonography and 92% for iuMRI (difference of 23%, 95% CI 18% to 27%); in the ≥ 24 weeks group, the figures were 65% for ultrasonography and 94% for iuMRI (difference of 29%, 95% CI 23% to 36%). Patient acceptability was high, with at least 95% of respondents stating that they would have iuMRI again in a similar situation. Health professional interviews suggested that iuMRI was acceptable to clinicians and that iuMRI was useful as an adjunct to ultrasonography, but not as a replacement. Across a range of scenarios, iuMRI resulted in additional costs compared with ultrasonography alone. The additional cost was consistently < £600 per patient and the cost per management decision appropriately changed was always < £3000. There is potential for reporting bias from the referring clinicians on the diagnostic and prognostic outcomes. Lower than anticipated follow-up rates at 3 years of age were observed. iuMRI as an adjunct to ultrasonography significantly improves the diagnostic accuracy and confidence for the detection of fetal brain abnormalities. An evaluation of the use of iuMRI for cases of isolated microcephaly and the diagnosis of fetal spine abnormalities is recommended. Longer-term follow-up studies of children diagnosed with fetal brain abnormalities are required to fully assess the functional significance of the diagnoses. Current Controlled Trials ISRCTN27626961. This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 23, No. 49. See the NIHR Journals Library website for further project information.